Influence of Orbital Shaking on Microstructure and Mechanical Properties of A380 Aluminium Alloy Produced by Lost Foam Casting - Kisasoz, Alptekin; Guler, Kerem Altug; Karaaslan, Ahmet (PLEIADES PUBLISHING INC, 2017)
Using vibration for refining microstructure and improve mechanical properties of aluminium alloys castings are in the interest of researchers for many years. Within the framework of these studies mechanical, ultrasonic and electromagnetic vibration applications were carried out. Results of these processes can be summarized as grain refining and changing the dendritic structure into globular. Accordingly increasing in density and mechanical properties were reported. In this work, orbital shaking technique was used alternatively to conventional mechanical vibration in lost foam casting (LFC) of A380 aluminium alloy. In the experiment castings, effects of shaking movement and speed during pouring were investigated. First of all orbital shaking movement has not damage LFC parts and any shape disorder was not occurred. Optical microstructure observations show that, the increase in shaking speed, decrease secondary dendrite arm spacing (SDAS) and partial dendrite arm fractures were determined at 150 rpm shaking. Density and hardness of as cast specimens were increased with shaking and rising shaking speed as well.
Keywords: Lost foam casting (LFC); orbital shaking; A380 alloy; mechanical vibration; ELECTROMAGNETIC VIBRATION; MAGNESIUM ALLOY; BEHAVIOR; Metallurgy & Metallurgical Engineering